2015
DOI: 10.1108/ijlss-08-2013-0047
|View full text |Cite
|
Sign up to set email alerts
|

An application of 5S concept to organize the workplace at a scientific instruments manufacturing company

Abstract: Purpose – The purpose of this paper is to use the 5S tool to assist a small-scale manufacturing organization to become more productive and more efficient. Design/methodology/approach – A simple approach has been adopted to create the teams for implementing 5S. Cause-and-effect diagram has been studied for shop floor analysis. Later, four data collection methods have been used to ensure right implementation of the 5S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 15 publications
0
27
0
11
Order By: Relevance
“…O quinto e último senso busca instituir comissões e grupos para criação e execução de modelos que auxiliem na manutenção do programa e na internalização dos demais sensos (GUPTA; JAIN, 2015). A autodisciplina está no hábito de respeitar todas as normas existentes na organização, sendo estas relativas aos demais sensos do programa.…”
Section: Senso De Autodisciplina-shitsukeunclassified
See 1 more Smart Citation
“…O quinto e último senso busca instituir comissões e grupos para criação e execução de modelos que auxiliem na manutenção do programa e na internalização dos demais sensos (GUPTA; JAIN, 2015). A autodisciplina está no hábito de respeitar todas as normas existentes na organização, sendo estas relativas aos demais sensos do programa.…”
Section: Senso De Autodisciplina-shitsukeunclassified
“…Os cinco princípios do programa focam na organização eficaz, simplificação do ambiente de trabalho e minimização de desperdícios, melhorando simultaneamente a qualidade e segurança (GUPTA; JAIN, 2015). A empresa júnior objeto deste estudo apresentou problemas na utilização e organização do seu espaço físico limitado, fazendo com que a aplicação do programa fosse justificável e viável.…”
Section: Introductionunclassified
“…The authors also reported that it is very essential to provide training of 5S technique to the employees. Gupta and Jain (2015) have examined that implementation of 5S at all the workstations of small scale organisation considerably reduced the tool searching time from 30 minutes to 5 minutes and make workplace efficiently productive. They analysed that 5S is a powerful tool which can be implemented in various industries whether it is micro, small, medium or large.…”
Section: Literature Surveymentioning
confidence: 99%
“…Seiri (organização) é a primeira etapa do 5S e o objetivo principal é eliminar itens desnecessários no local de trabalho (Gupta & Jain, 2015). Seiton (arrumar) garante um lugar para cada parte, focando na segregação dos objetos e sua efetiva estocagem (Harrington, 2000).…”
Section: Sunclassified
“…Uma área organizada e limpa é um fator de motivação para os colaboradores. Seiketsu (padronização) visa garantir um alto padrão de organização do ambiente de trabalho (Gupta & Jain, 2015). Shitsuke (disciplina) tem como objetivo sustentar a padronização alcançada que deve ser preservada de uma maneira efetiva (Harrington, 2000;Dudek -Burlikowask, 2006).…”
Section: Sunclassified